PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS XI IPS SMA NEGERI 7 TAMBUN SELATAN PADA MATERI DINAMIKA PENDUDUK - Sari, Shintya Novita (Universitas Nusa Cendana, 2024)
The purpose of this research is to find out whether ther is an affect of the Creative Problem Solving learning model on student’s creative thiking skill at SMA Negeri 7 Tambun Selatan. This type of quasi experimental research with randomized post-test only controlled group design. The population of this study was all student of class XI IPS which consist of 3 classes total 111 students. The sampling technique used a random sampling. Class of XI IPS 2 as the control grup and class of XI IPS 3 as the experiment class. Data taken by test and documentation techniques. Data analyzed by independent t test on post-test score of XI IPS 2 as control group and XI IPS 3 as experiment class. Previously the data were tested for normality and homogenity test. The results showed that there was an influence in the application of the Creative Problem Solving model on student’s creative thiking skill at SMA Negeri 7 Tambun Selatan with the results of independent t test of > that 2,494 > 1,997.